Analysis of Shallow Groundwater Quality as Consumable Water in Maros Baru District Aquifer Systems, South Sulawesi, Indonesia - Emi Prasetyawati Umar; Alfian Nawir; Hariani M. Pakka; Jamaluddin Jamaluddin; Nurfadhilah Sam Tappa; Watcharin Joemsittiprasert (CV FOUNDAE, 2022)
Water is a source of necessity for humans. Water quality is very important to be considered as the source of clean water. Some people in Maros Baru District use ground wells as the source of water needs. Therefore it is important to know the physical quality and pH level of shallow wells and to know the worthiness of shallow wells in Maros Baru District with reference to Permenkes No.492/ 2010. This study examined the feasibility of water based on the physical quality and the pH level of water taken from shallow wells. The research was carried out directly in field with 14 sampling points scattered in the north, east, south, west and at the center of field. The method in observing pH value is by litmus paper and observation on the physical condition of water, well depth, well diameter and surface level of water. The result shows there were 2 locations with saltwater taste, as the location is near from the sea and rivers, while turbidity of the water influenced by condition of surround environment that was not properly maintained. From data processing, it can be concluded that as many as 5 of the 14 sampling points did not meet the eligibility standards of Permenkes No.492/2010 to be used as a source of clean water intended for drinking water.